Perceived social support partially mediates the association between childhood abuse and pain-related characteristics - Pierce, Jennifer; Presto, Jacob; Hinckley, Elizabeth; Hassett, Afton L.; Dickens, Joseph; Schneiderhan, Jill R.; Grace, Kathryn; McAfee, Jenna (Frontiers in Pain Research, 2022)
Higher perceived social support has been shown to buffer the impact of negative stressful events like childhood abuse on health outcomes. Yet, the role of perceived social support as a mediator of the association between childhood abuse and pain-related characteristics is not well understood. The present study explored this premise. Patients (n = 1,542) presenting to a tertiary-care, outpatient pain clinic completed a cross-sectional survey consisting of regularly collected clinical data and validated measures. Path analysis suggested that the impact of childhood abuse on sensory and affective pain-related characteristics was partially explained by perceived emotional support. Survivors of childhood abuse display a more complex clinical pain phenotype and this extends to more negative perceptions of social support. Our findings may reflect processes whereby childhood abuse negatively impacts social relationships across the lifespan, and these negative social perceptions and relationships influence sensory and affective components of pain.